Células mucosas branquiais de Hemigrammus Levis Durbin, 1908 como Biomarcadoras ambientais no Lago Juá, Santarém, PA, Brasil. - SANTOS, Tatiane da silva (Universidade Federal do Oeste do Pará, 2019)
Water pollution is one of the major environmental problems of today and the aquatic biota is one of the most affected by urban development. Fish are extremely sensitive animals, as they can be contaminated through the direct absorption of substances from the environment by the gills or food ingested. The objective of this research was to evaluate the mucous cells of Hemigrammus levis collected in Lake Juá, Santarém, Pará, Brazil, as environmental biomarkers, in addition to correlating the density of the cells with the physical-chemical variables of lake water. The sampling points (1 and 2) were defined based on geographic difference and based on previous environmental impact information and also used for water collection. Point 1 was located near an anthropic area and point 2 was near the most preserved area. Flona (Tapajós National Forest) was also used as the control environment. Samples were collected for 12 months, from April 2017 to March 2018. Fish (n = 130, standard length (cm) 3.43 ± 4.2, weight (g) 0.73 ± 0.24) were placed in plastic bags with constant aeration before biometry and anesthetized in eugenol solution (100 mg / L) to be submitted to the dissection and histological procedure of the gills, in addition to marking the cells. The sections were stained using Alcian Blue pH-2.5, Periodic Acid and Shiff React solution. The gill mucosa cells were identified and quantified with the aid of a microscope coupled with an image capture system and interactive measurement program, thus obtaining cell density in mm². The water variables evaluated were pH, temperature, dissolved oxygen, electrical conductivity, sodium, potassium, chloride, ammonia, hardness and alkalinity, submitted to Pearson correlation analysis and regression. The mucosal cell density was analyzed from the MannWhitney Test. The analysis of water variables showed higher values of conductivity over a year at point 1.Flona's variables approached point 2, with a higher concentration of dissolved oxygen and lower electrical conductivity, suggesting a preserved environment. In the species analyzed, it was observed that the density of acidic and neutral mucosal cells was modulated by the changes that occurred in the physicochemical variables of water, especially in the low water period. The data suggest that pH and potassium are the most important variables for this purpose. Therefore, it is suggested that Hemigrammus levis is a potential species to be visualized as an environmental quality bioindicator of Lake Juá, since it showed modulation of mucous cells in the face of environmental changes. Key words: anthropization, biomonitoring, gills, fish
Keywords: Antropização; Biomonitoramento; Brânquias; Peixes; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; Ecofisiologia de organismos aquáticos